Estimativas das interações biosfera-atmosfera em ecossistema de pastagem natural do biompa Pampa - Acosta, Ricardo (2019)
The Pampa biome and its ecosystems play a significant environmental role by providing services such as climate regulation and carbon sequestration. This research looks at and answers some relevant scientific questions and contributes to the understanding of how this important ecosystem fits into the context of climate system studies. The experimental site of Santa Maria, established by the PELD/CSUL network, brings together the fundamental characteristics for studies of the most diverse areas of knowledge, in what is the main landscape of Pampa, the native pasture. The micrometeorological technique used presented an energy balance closure (LE+H vs FG+RN) of 75%, with r 2 = 0.9. The Net Radiation (RN) has a seasonality that notably follows the incident RG. The use of this energy by the ecosystem differs throughout the year in two phases. One where latent heat flow is dominant over sensitive heat flow, occurs between August and April. Another phase, when RN is smaller (~ 75 W m-2), sensitive heat is dominant, occurs between May and July. Regarding biophysical processes involving carbon exchange between biosphere-atmosphere, the Gross Primary Production (GPP) presented annual variability between 2,285 gC m-2 year -1 and 2,902 gC m-2 year -1 in the photosynthetic process and Ecosystem Respiration (RECO) ranged from 2,124 gC m-2 year -1 to 2,477 gC m-2 year -1 . The average ratio between RECO and GPP for the entire period was 86% and indicates the capacity of the ecosystem to act as a sink in the annual net balance. Annual carbon estimates, or Net Ecosystem Productivity (NEP), in the January-December balance of analysis showed a positive sign. The annual variability showed values ranging between +109.4 gC m-2 year -1 (2014) and +507.2 gC m-2 year -1 (2015), with average annual value for the 5 complete years analyzed, of +349 gC m-2 year -1 . This result implies that the natural grassland ecosystem acts as an atmospheric carbon sink.